Predicting the hyperelastic properties of alginate-gelatin hydrogels and 3D bioprinted mesostructures - Ahmadi Soufivand, Anahita; Budday, Silvia (Scientific Reports, 2023)
Additive manufacturing has been widely used in tissue engineering, as 3D bioprinting enables fabricating geometrically complicated replacements for different tissues and organs. It is vital that the replacement mimics the specific properties of native tissue and bears the mechanical loading under its physiological conditions. Computational simulations can help predict and tune the mechanical properties of the printed construct—even before fabrication. In this study, we use the finite element (FE) method to predict the mechanical properties of different hydrogel mesostructures fabricated through various print patterns and validate our results through corresponding experiments. We first quantify the mechanical properties of alginate-gelatin hydrogels used as matrix material through an inverse approach using an FE model and cyclic compression-tension experimental data. Our results show that the fabrication process can significantly affect the material properties so that particular caution needs to be paid when calibrating FE models. We validate our optimized FE model using experimental data and show that it can predict the mechanical properties of different mesostructures, especially under compressive loading. The validated model enables us to tune the mechanical properties of different printed structures before their actual fabrication. The presented methodology can be analogously extended for cell bioprinting applications, other materials, and loading conditions. It can help save time, material, and cost for biofabrication applications in the future.
CRIS-Team Scopus Importer:2023-12-22